Features of precedent texts in hypertext (Eurasian Journal of Philology Science and Education, 2018)
The article considers the problems of semantic organization of modern mass media texts, which isa hypertext. The precedent texts, along with intertextuality, are means of expressing of the intertextualinteraction in the hypertext. The precedent text stands for the frequently quoted texts that are significantfor members of a particular culture (the lines of popular works, proverbs, idioms, quotations from literaryworks, aphorisms, lines from songs, etc.). The main function of precedent texts is not only to inform thereader or listener, but the impact on him/her, shaping a certain opinion about a particular event, situation.An indicator of activity of precedent texts in modern mass media text is the frequency of usageof the same original texts, while the studied text-precedents become a model according to which newlinguistic units are produced. The factual material are domestic Russian-language press.Key words: precedenttext, hypertext, Internet, links, intertextuality, postmodernism.